Optimalisasi Peran Orang Tua Sebagai Gate Keeper Dalam Membentuk Identitas Diri Anak di Era Internet - Musa, Dahniar Th.; Marbun, Posmanto; Mutmainnah, Mutmainnah; Larasati, Azizah (Puslitbang Sekawan Institute Nusa Tenggara, 2026)
The development of information technology, especially the internet, makes it easy for children and adolescents to access various kinds of information. However, without parental supervision, this can potentially influence the formation of their identity. This study aims to optimize the role of parents as gatekeepers in shaping children's identity in the internet era. Parents are expected to control and supervise their children's access to digital information that can influence their development. The method used in this study consists of several stages of preparation, implementation, and evaluation, in which this Community Service (PkM) activity was carried out in Sungai Ambawang District, Kubu Raya Regency. This activity involved parents who are also members of the Family Welfare Empowerment (PKK) to increase their understanding of the role of gatekeepers in the family. The results of the community service showed an increase in parents' knowledge about the importance of supervising their children's use of gadgets and their role in providing moral and social values in accordance with local culture. However, challenges such as difficulties in regulating the use of gadgets still exist. It is hoped that synergy between parents and children can be created to foster a more prudent environment in the use of technology and social media.